Pengaruh Efikasi Diri terhadap Kebugaran dan Kualitas Hidup pada Mahasiswa Pendidikan Jasmani - Hidayah, M. Alif Rahmad; Santoso, Januar Abdilah; Jusuf, Jeane Betty Kurnia (Universitas Hamzanwadi, 2025)
Self-efficacy significantly influences the adoption and maintenance of health behaviors; yet, researchers have not adequately examined its effects on physical fitness and quality of life among physical education students. This correlational study examined the relationship between exercise self-efficacy, cardiorespiratory endurance, and life satisfaction among young physical education students (N=86, ages 18-25) at Muhammadiyah University of East Kalimantan. Participants completed the WHOQOL-BREF quality of life questionnaire, the Exercise Self-Efficacy Scale, and the Multistage Fitness Test for vo2max evaluation. Self-efficacy exhibited significant positive correlations with cardiorespiratory fitness (r=0.612, p<0.001). The quality of existence had a significant link with self-efficacy (r=0.578, p<0.001). Regression analysis revealed that self-efficacy accounted for 37.5% of the variance in cardiorespiratory fitness and 33.4% of quality of life ratings. Self-efficacy exhibited a stronger correlation with the physical and psychological dimensions of quality of life (r=0.593 and r=0.602). It exhibited a tenuous affiliation within environmental and social dimensions. These findings underscore the importance of self-efficacy enhancement measures in physical education curriculum to enhance physical fitness and quality of life among university students, particularly as they acquire lifelong health practices during this crucial developmental phase.